Nanodiamond-DGEA peptide conjugates for enhanced delivery of doxorubicin to prostate cancer - Salaam, Amanee D; Hwang, Patrick; McIntosh, Roberus; Green, Hadiyah N; Jun, Ho-Wook; Dean, Derrick (Beilstein Journal of Nanotechnology, 2014)
The field of nanomedicine has emerged as an approach to enhance the specificity and efficacy of cancer treatments as stand-alone therapies and in combination with standard chemotherapeutic treatment regimens. The current standard of care for metastatic cancer, doxorubicin (DOX), is presented with challenges, namely toxicity due to a lack of specificity and targeted delivery. Nano-enabled targeted drug delivery systems can provide an avenue to overcome these issues. Nanodiamonds (ND), in particular, have been researched over the past five years for use in various drug delivery systems but minimal work has been done that incorporates targeting capability. In this study, a novel targeted drug delivery system for bone metastatic prostate cancer was developed, characterized, and evaluated in vitro. NDs were conjugated with the Asp–Gly–Glu–Ala (DGEA) peptide to target α2β1 integrins over-expressed in prostate cancers during metastasis. To facilitate drug delivery, DOX was adsorbed to the surface of the ND-DGEA conjugates. Successful preparation of the ND-DGEA conjugates and the ND-DGEA+DOX system was confirmed with transmission electron microscopy, hydrodynamic size, and zeta potential measurements. Since traditional DOX treatment regimens lack specificity and increased toxicity to normal tissues, the ND-DGEA conjugates were designed to distinguish between cells that overexpress α2β1 integrin, bone metastatic prostate cancers cells (PC3), and cells that do not, human mesenchymal stem cells (hMSC). Utilizing the ND-DGEA+DOX system, the efficacy of 1 µg/mL and 2 µg/mL DOX doses increased from 2.5% to 12% cell death and 11% to 34% cell death, respectively. These studies confirmed that the delivery and efficacy of DOX were enhanced by ND-DGEA conjugates. Thus, the targeted ND-DGEA+DOX system provides a novel approach for decreasing toxicity and drug doses.
Keywords: DGEA peptide; doxorubicin; nanodiamond; prostate cancer; targeted drug delivery